2022
DOI: 10.3390/ijerph19031795
|View full text |Cite
|
Sign up to set email alerts
|

Internet Use and Quality of Life: The Multiple Mediating Effects of Risk Perception and Internet Addiction

Abstract: The impact of internet use on quality of life (QoL) has become an increasing focus of academic research. This paper aims to explore the internal influencing mechanisms of internet use (i.e., leisure-oriented internet use (LIU); work-oriented internet use (WIU)) on QoL, with a focus on the multiple mediating effects of risk perception and internet addiction. We constructed a theoretical framework from a psychological perspective and tested the hypotheses using hierarchical regression analysis with a sample of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…However, the link between Internet addiction and adolescents’ QoL remains debatable. Previous studies indicated that Internet addiction is negatively associated with high QoL among adolescents as they escape from reality, which may reduce their interpersonal resources and developing opportunities [ 34 , 35 ]. Nevertheless, Tran and his colleagues [ 36 ] argued that being addicted to network activities allows adolescents to satisfy their psychological and social demands and may positively predict high QoL, which has been suggested empirically [ 37 , 38 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the link between Internet addiction and adolescents’ QoL remains debatable. Previous studies indicated that Internet addiction is negatively associated with high QoL among adolescents as they escape from reality, which may reduce their interpersonal resources and developing opportunities [ 34 , 35 ]. Nevertheless, Tran and his colleagues [ 36 ] argued that being addicted to network activities allows adolescents to satisfy their psychological and social demands and may positively predict high QoL, which has been suggested empirically [ 37 , 38 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, in a study [ 27 ], a group intervention focused on boosting PsyCap caused significant improvements in mental well-being and reductions in depression among Chinese university students. These findings emphasize the potential benefits of integrating PsyCap development into higher education MH strategies in China.…”
Section: Introductionmentioning
confidence: 99%
“…The virus was highly transmissible and contagious [ 24 ], causing “fear” [ 25 ] and negative emotions among Chinese college students [ 26 ]. Previous studies have suggested that individuals’ perception of risk is one of the drivers of Internet addiction behavior [ 27 ], and it may also cause individuals’ difficulties in emotion regulation [ 28 ]. Recent studies have confirmed that difficulties in emotion regulation are also an important contributing factor to Internet addiction among college students [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study in Nigeria noted that college students were at an increased risk of Internet addiction during the COVID-19 epidemic and found higher levels of Internet addiction among students in EKSU (public universities) or liberal arts colleges [ 46 ]. Several recent studies have shown that the COVID-19 perceived risk is positively associated with Internet addiction in different populations [ 4 , 23 , 27 , 48 ]. One study conducted in outbreak-controlled regions in China further revealed that the COVID-19 risk perception was significantly positively associated with Internet addiction among college students experiencing campus lockdown, and COVID-19 perceived risk could positively predict Internet addictive behavior [ 23 ].…”
Section: Introductionmentioning
confidence: 99%